I risultati scolastici: alcune piste di approfondimento III Seminario "I dati INVALSI: uno strumento per la ricerca" - Falzetti, Patrizia (INVALSI per la Ricerca, 2021)
INVALSI Statistical Service has been organizing the Seminar "INVALSI data: a research tool" for many years. It's an event which is becoming more and more important for all those who have an interest in discussing and sharing ideas, studies and experiences, from different points of view, about what INVALSI data could tell for teaching and research to several stakeholders. In this issue, the main core topic is about academic achievement and its conditioning factors. Educational results are both outcomes of single student's engagement and consequence of a more complex process which involves the family, the school community and the wider context. This book has ten chapters and it includes some studies and researches, based on different theoretical and methodological approaches, made during the III edition of the Seminar, held in Bari from 26th to 28th October 2018, which could be a helpful insight in order to explore and deepen the main issue.